The Influence of Work Discipline and Physical Work Environment on Employee Performance at PT. Mayora Indah Tbk - Azahra, Alyssa Aulia; Hia, Era Era; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the simultaneous influence of Work Discipline and the Physical Work Environment on employee performance at PT Mayora Indah Tbk.This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all employees of PT Mayora Indah Tbk. The sample size was 100 respondents. This study used a saturated sampling technique due to the relatively small population size; therefore, the entire population of 100 employees was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis employed multiple linear regression analysis using SPSS 31. Data validity was verified through partial t-tests and simultaneous F-tests.The results of this study indicate that (1) Partially, work discipline does not significantly affect employee performance at PT Mayora Indah Tbk, as indicated by a calculated T value > T table (1.186 < 1.975) and a significance value of 0.239 greater than the 0.05 value. Therefore, H0 is accepted and Ha is rejected. (2) Partially, the physical work environment significantly affects employee performance at PT Mayora Indah Tbk, as indicated by a calculated T value > T table (3.674 > 1.975) and a significance value of 0.000 less than the 0.05 value. Therefore, H0 is rejected and Ha is accepted. (3) Simultaneously, work discipline and the physical work environment significantly affect employee performance at PT Mayora Indah Tbk, as indicated by a calculated F value > F table (14.131 > 3.09) with a significance value of 0.001. Therefore, H0 is rejected and Ha is accepted.Based on the research results, it can be concluded that the variables of Work Discipline and Physical Work Environment, both partially and simultaneously, have a significant influence on employee performance at PT Mayora Indah Tbk.